2023
DOI: 10.1371/journal.pone.0279756
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic analysis based on whole genome sequence of bovine leukemia virus in cattle under 3 years old with enzootic bovine leukosis

Abstract: Enzootic bovine leukosis (EBL) is one of bovine neoplasms caused by bovine leukemia virus (BLV). Although EBL is typically observed in cattle over 3 years old, several cases of EBL onset in cattle under 3 years old have been reported in Japan. The mechanism for EBL onset in young cattle remains unclear. Although genetic variation of BLV is limited, the variations could affect viral properties relating to BLV pathogenesis. The purpose of this study was to clarify relationship between early onset of EBL and BLV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Экспрессия вирусных генов индуцируется на транскрипционном уровне при помощи трансактиватора Tax, кодируемого вирусом [14]. Белок Tax функционирует как трансактиватор транскрипции вирусных генов и модулирует экспрессию некоторых клеточных генов хозяина [15]. Таким образом, считается, что белок Tax играет критическую роль в процессе лейкемогенеза, вызываемого дельтавирусами [16].…”
Section: организация генома вируса Blvunclassified
“…Экспрессия вирусных генов индуцируется на транскрипционном уровне при помощи трансактиватора Tax, кодируемого вирусом [14]. Белок Tax функционирует как трансактиватор транскрипции вирусных генов и модулирует экспрессию некоторых клеточных генов хозяина [15]. Таким образом, считается, что белок Tax играет критическую роль в процессе лейкемогенеза, вызываемого дельтавирусами [16].…”
Section: организация генома вируса Blvunclassified
“…BLV is divided into 5 groups (A, B-1, B-2, C, and other) according to its complete genome sequence. BLV in EBL cattle under 3 years of age is mainly classified as Group A or B-1 [ 5 , 11 ], and previous studies have reported no Group C strain in EBL cattle. In fact, Group C BLV has only been isolated from cattle without EBL [ 5 , 7 , 11 ].…”
mentioning
confidence: 99%
“…BLV in EBL cattle under 3 years of age is mainly classified as Group A or B-1 [ 5 , 11 ], and previous studies have reported no Group C strain in EBL cattle. In fact, Group C BLV has only been isolated from cattle without EBL [ 5 , 7 , 11 ]. Here we report a clinical case of EBL caused by BLV classified as Group C in a 23-month-old Holstein-Friesian heifer with no enlargement of lymph nodes or masses in the pelvic cavity.…”
mentioning
confidence: 99%
See 2 more Smart Citations